2020
DOI: 10.1111/are.14501
|View full text |Cite
|
Sign up to set email alerts
|

Effect of partial replacement of dietary fish meal by soybean meal with betaine attractant supplementation on growth performance and fatty acid profiles of juvenile rainbow trout (O ncorhynchus mykiss )

Abstract: This study was conducted to investigate the effects of dietary incorporation of soybean meal for fish meal replacement and supplementation of betaine as an attractant on growth performance and fatty acid profiles of rainbow trout (Oncorhynchus mykiss). Juvenile trout were fed practical diets, with increasing soybean levels and betaine supplementations. The experimental diets consisted of a control diet with fish meal as the sole protein source (control) and no attractant, 25% soybean‐1% betaine diet (SBM25‐B1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 32 publications
2
14
0
Order By: Relevance
“…In particular, farmed fish contain important amounts of health-promoting long-chain omega-3 FAs such as eicosapentaenoic (EPA) and docosahexaenoic (DHA) acids when fed on FM- and FO-formulated diets, but those decreased when fed diets formulated with sustainable alternatives of terrestrial origin [ 75 ]. Here, the n-3/n-6 ratio to assess the nutritional value of the fillet showed values within the reported range for rainbow trout and other salmonid species, from 0.90 to 1.38 [ 13 , 76 ]. Food items with values higher than 1 in this ratio are considered to reduce the risk of cardiopathies, as well as inflammatory and immunological diseases [ 77 , 78 , 79 , 80 ].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In particular, farmed fish contain important amounts of health-promoting long-chain omega-3 FAs such as eicosapentaenoic (EPA) and docosahexaenoic (DHA) acids when fed on FM- and FO-formulated diets, but those decreased when fed diets formulated with sustainable alternatives of terrestrial origin [ 75 ]. Here, the n-3/n-6 ratio to assess the nutritional value of the fillet showed values within the reported range for rainbow trout and other salmonid species, from 0.90 to 1.38 [ 13 , 76 ]. Food items with values higher than 1 in this ratio are considered to reduce the risk of cardiopathies, as well as inflammatory and immunological diseases [ 77 , 78 , 79 , 80 ].…”
Section: Discussionsupporting
confidence: 76%
“…Nevertheless, several issues have limited the use of these alternative protein sources, such as the presence of antinutritional factors (ANFs), phytoestrogens and non-soluble carbohydrates, the lower digestibility of crude protein and bioavailability of minerals and/or the deficiencies in some amino acids, among other factors [ 9 , 10 , 11 ]. Soybean ( Glycine max ) meal (SBM) stands as the most used alternative raw material to substitute FM (up to 20–40%), among the other vegetable protein sources considered [ 7 , 12 , 13 ]. Most of SBM is produced in the USA, Argentina and Brazil and thus, European aquaculture largely depends on importation from third countries [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…This could be related to diversity in lipid metabolism of different fish species during different development stages, since our study included many fish species at different developmental stages. A range of aquaculture and experimental studies indicate that EPA and DHA supplement increase fish individual growth and to some extent the muscle FA content of adult fish (Bou et al., 2017; Yeşilayer & Kaymak, 2020). However, similar evidence from the wild is very difficult to obtain due to limited food resources, slow growth rate of fish, long turnover time of muscle tissue, reproduction cycle and species‐specific differences in lipid storages (Jørgensen et al., 1997; Keva et al., 2019; Thomas & Crowther, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…An important subgroup of lipids are polyunsaturated fatty acids (PUFAs), providing essential components for cell development and functioning; however, the distribution of lipids and fatty acids varies greately among taxa and trophic levels. While there are several PUFAs, eicosapentaenoic acid (20:5n-3, EPA) and docosahexaenoic acid (22:6n-3, DHA) are considered the most important since they are essential for growth, neural development and reproduction of consumers (Arts et al, 2001;Bou et al, 2017;Yeşilayer & Kaymak, 2020). Only certain algae groups, such as dinoflagellates, diatoms and cryptophytes, are able to produce EPA and DHA efficiently and are abundant in cold and nutrient-poor lakes (Taipale et al, 2013(Taipale et al, , 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Mackie and Mitchell (1982) found that the feeding stimulant requirement of the Dover sole was very specific and only betaine and dimethylthetin proved to be effective. Yeşilayer and Kaymak (2020) investigated the effect of partial replacement of dietary fish meal by soybean meal with betaine attractant supplementation on juvenile rainbow trout and concluded that 1% betaine supplementation with dietary incorporation of soybean meal at 25% level positively influenced growth performance, feed utilization and fatty acid profiles of rainbow trout juveniles. The last two studies mentioned above are indicating that that the prosperous era of betaine commencing in the eighties of the last century is continuing until these days.…”
Section: Purified or Synthetic Substances As Feeding Stimulantsmentioning
confidence: 99%